SERTIFIKASI KEAHLIAN PETUGAS PROTEKSI RADIASI (PPR) DAN CT SCAN DASAR TERHADAP PENYERAPAN LULUSAN DI DUNIA KERJA - Edy Susanto; Emi Murniati; Agung Nugroho Setiawan (Jurnal Riset Kesehatan, 2016)
This research aims to analyze the skills certification in Radiation Protection Officer (PPR) and Basic CT Scan for graduates in relation with the absorption of graduates employment. The type of research is descriptive qualitative study approach. Subjects were graduates from Diploma program of TRR Semarang and Purwokerto, specialist doctors and radiographers as users of graduates. Data taken from observation and check list/survey of alumni, interviews and focus group discussions. The results of this research are skills certification of Radiation Protection Officer (PPR) provides benefits in terms of radiation protection skills and provide more value when applying on the job. In addition, the ability in the field of radiation protection will ensure radiation safety for patients, radiation workers and community/environment. Basic CT Scan skills certification provides benefits in operating aircraft proficiency CT scans, particularly on the basis of the examination, as add value of graduates and make graduates quickly adjust to working conditions.